Pengaruh Edukasi Menyusui terhadap Efektivitas Menyusui (Metode LATCH) pada Ibu Nifas dengan Bayi Lip-Tie di Rumah Sakit Krakatau Medika Cilegon - Annisa Nurhayati Hidayat; Husnul Khotimah; Indah Nurfazriah (PPNI UNIMMAN, 2025)
Breastfeeding success often faces various challenges, one of which is the infant’s anatomical condition, such as a lip tie. Successful breastfeeding can be achieved if mothers and infants develop good breastfeeding skills, including correct LATCH technique. This study aims to determine the effect of breastfeeding education on breastfeeding effectiveness using the LATCH method among postpartum mothers with infants with lip tie at Krakatau Medika Hospital Cilegon. The research design was a quasi-experiment with a one-group pretest–posttest approach. The study population included all breastfeeding mothers with infants diagnosed with lip tie, with a total sample of 29 participants selected through accidental sampling. The results showed that the rate of effective breastfeeding with good attachment before the education was 13.8% and increased to 41.4% after the education, with the mean breastfeeding effectiveness score rising from 4.86 to 6.97. The paired t-test revealed a significant difference between LATCH scores before and after the education (p < 0.001). It is recommended that Krakatau Medika Hospital develop a standard operating procedure (SOP) for breastfeeding education using the LATCH method.